Q‐space truncation and sampling in diffusion spectrum imaging. Issue 6 (13th January 2016) - Tian, Qiyuan; Rokem, Ariel; Folkerth, Rebecca D.; Nummenmaa, Aapo; Fan, Qiuyun; Edlow, Brian L.; McNab, Jennifer A.
Abstract : Purpose: To characterize the q‐space truncation and sampling on the spin‐displacement probability density function (PDF) in diffusion spectrum imaging (DSI). Methods: DSI data were acquired using the MGH‐USC connectome scanner ( G max  = 300 mT/m) with b max  = 30, 000 s/mm 2, 17 × 17 × 17, 15 × 15 × 15 and 11 × 11 × 11 grids in ex vivo human brains and b max  = 10, 000 s/mm 2, 11 × 11 × 11 grid in vivo. An additional in vivo scan using b max =7, 000 s/mm 2, 11 × 11 × 11 grid was performed with a derated gradient strength of 40 mT/m. PDFs and orientation distribution functions (ODFs) were reconstructed with different q‐space filtering and PDF integration lengths, and from down‐sampled data by factors of two and three. Results: Both ex vivo and in vivo data showed Gibbs ringing in PDFs, which becomes the main source of artifact in the subsequently reconstructed ODFs. For down‐sampled data, PDFs interfere with the first replicas or their ringing, leading to obscured orientations in ODFs. Conclusion: The minimum required q‐space sampling density corresponds to a field‐of‐view approximately equal to twice the mean displacement distance (MDD) of the tissue. The 11 × 11 × 11 grid is suitable for both ex vivo and in vivo DSI experiments. To minimize the effects of Gibbs ringing, ODFs should be reconstructed from unfiltered q‐space data with the integration length over the PDF constrained to around the MDD. Magn Reson Med 76:1750–1763, 2016. © 2016 International Society for Magnetic Resonance in Medicine